Blind Cane Using 2 Axis Servo with Fuzzy Logic Method - Sumardi Sumardi; Sudarti Sudarti; Arizal Mujibtamala Nanda Imron; Wahyu Muldayani (Postgraduate, University of Mataram, 2022)
Based on data from the Ministry of Health and the Central Bureau of Statistics, it is known that the number of people with disabilities, especially the visually impaired, is 1-1.5% of the total 237 million Indonesian population, which is around 3.75 million blind people. A tool often used to accommodate them is a cane used to feel the ground if there are downgrade and obstructions in front of them. In this study, researchers developed the previous research on blind cane using a 2 axis servo. It was classified using the Fuzzy Logic programming method, which was processed using the Arduino Nano 328P microcontroller. The results of the test on respondents with visual impairments were that they feel accommodating with the tool because the cane users can easily find obstructions with the Navigation Instruction so that they can easily avoid Static obstructions (Static Objects).